The Development of Digital Competence Model Among TVET Educators Towards Digitization: A Concept Paper - Md Hani, Mohd Hatta; Affero Ismail; Siti Soleha Razali; M. Nizan Abu Bakar; Nur Liyana Rosman; Nuqman Nasir; Zawawi Mohamad (Journal of TVET and Technology Review, 2024)
The ongoing trend towards digitization in education has introduced new challenges for educators, necessitating a range of competencies to meet contemporary demands. Technical and Vocational Education and Training (TVET) educators are no exception to these challenges. To ensure the production of high-quality students, educators must develop digital competencies that are critical for effective technology integration in education. In recent years, the Malaysian government has strongly emphasized the importance of TVET in preparing the workforce for the demands of the Fourth Industrial Revolution (IR4.0). However, studies have revealed that TVET educators in Malaysia often struggle to keep up with the rapidly evolving digital landscape, lacking the necessary competencies to integrate technology into their teaching practices effectively. To address this issue, developing a comprehensive model for digital competencies among TVET educators within the Malaysia Technical University Networks (MTUN) is crucial. Several International frameworks for digital competence exist, allowing educators to assess their skills, identify training needs, and receive targeted training. However, a specific digital competency model for TVET educators is currently lacking. From observation, interviews, and previous research, it was found that there is a need for a structured digital competence model for TVET educators to integrate digital technologies into teaching and learning effectively. This research aims to explore the current state of digital competencies among TVET educators in Malaysia, identify the key factors contributing to developing these competencies, and propose a framework for effectively implementing a digital competencies model. Utilizing the Exploratory Sequential Mixed Methods approach, the study was conducted in two phases: the first phase involved document analysis and structured interviews with ten experts in educational technology and digitization to identify the domains and elements of digital competence among TVET educators. Theme analysis was employed to extract themes from the data, and the Fuzzy Delphi Method (FDM) was used to reach consensus among experts. In the second phase, a survey was conducted with 85 TVET educators from the Malaysian Technical Universities Network (MTUN). The survey data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to predict the relevant domains and elements. The findings revealed several domains, elements, and sub-elements of digital competence. Based on these findings, a digital competency model for TVET educators was developed. In conclusion, developing a digital competence model tailored specifically for TVET educators is crucial. This model will address the unique demands of vocational education, enhance teaching and learning outcomes, support effective digitization initiatives, and ensure the delivery of high-quality, industry-relevant education. Equipping TVET educators with the necessary digital skills and competencies will better prepare students for the challenges of the modern workforce and contribute to the overall advancement of the education system. This model is expected to play a vital role in developing competent and high-quality TVET educators in the future.